已知x^2+xy=6,y^2+xy=10 求(1)(x+y)^2 (2)x^2-y^2 (3)(x-y)2已知x^2+xy=6,y^2+xy=10 求(1)(x+y)^2 (2)x^2-y^2 (3)(x-y)^2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 10:40:58
已知x^2+xy=6,y^2+xy=10求(1)(x+y)^2(2)x^2-y^2(3)(x-y)2已知x^2+xy=6,y^2+xy=10求(1)(x+y)^2(2)x^2-y^2(3)(x-y)^
已知x^2+xy=6,y^2+xy=10 求(1)(x+y)^2 (2)x^2-y^2 (3)(x-y)2已知x^2+xy=6,y^2+xy=10 求(1)(x+y)^2 (2)x^2-y^2 (3)(x-y)^2
已知x^2+xy=6,y^2+xy=10 求(1)(x+y)^2 (2)x^2-y^2 (3)(x-y)2
已知x^2+xy=6,y^2+xy=10 求(1)(x+y)^2 (2)x^2-y^2 (3)(x-y)^2
已知x^2+xy=6,y^2+xy=10 求(1)(x+y)^2 (2)x^2-y^2 (3)(x-y)2已知x^2+xy=6,y^2+xy=10 求(1)(x+y)^2 (2)x^2-y^2 (3)(x-y)^2
(x+y)^2
=x^2+2xy+y^2
=x^2+xy+y^2+xy
=6+10
=16
x^2-y^2
=x^2+xy-(y^2+xy)
=6-10
=-4
(x-y)^2
=((x^2-y^2)/(x+y))^2
=(x^2-y^2)^2/(x+y)^2
=(-4)^2/16
=1
(X+Y)² =X²+2XY+Y² =6+10 =16
X²+XY -(Y²+XY) =X²-Y² =6-10 =-4
(x+y)^2=x^2+xy+y^2+xy=6+10=16
x^2-y^2=x^2+xy-(y^2+xy)=6-10=-4
(x-y)^2=x^2+y^2-2xy=x^2+y^2+2xy-4xy=(x+y)^2-4xy=16-4X(-4)=32
已知X+y=6,xy=7 求x^2y+xy^2=已知X+y=6,xy=7 x^2y+xy^2
已知x-xy=10,xy-y=2,则x-y=( ),-2xy+x+y=( ).
已知x-xy=20,xy-y=-10,则x-y=( ),x+y-2xy=( ).
已知x-xy=20,xy-y=-10,则x-y=?,x+y-2xy?
已知xy/x+y=6,求3x-2xy+3y/-x+3xy-y的值.
已知(xy)/(x+y)=6求(3x-2xy+3y)/(-x+3xy-y)的值.
已知1/x-1/y=2,求3x+7xy-3y/2x-3xy-2y答案是1/x-1/y=2(y-x)/xy=2 得:x-y=-2xy(3x+7xy-3y)/(2x-3xy-2y)=[3(x-y)+7xy]/[2(x-y)-3xy]=(-6xy+7xy)/(-4xy-3xy)=xy/(-7xy)=-1/7 谁能帮我解释一下=[3(x-y)+7xy]/[2(x-y)-3xy]=(-6xy+7xy)/(-4xy-3xy) 是怎
已知x+y=1,xy=-2,则x²y+xy²-2xy
已知x-xy=8,xy-y=-9,求x+y-2xy的值
已知:x/y=-2,求x^2-2xy-3y^2/x^-6xy
已知x/y=2,求 [x^2-xy+3xy^2 ] / [ x^2+xy+6y^2]的值
已知x+y=-2,求代数式(6xy+10y)+[4x-2(3xy+2y-x)]
由已知x+y=-2,xy=3那么2(x+xy)-[(xy-3y)-x]-(-xy)等于多少?
已知2x+xy=10,3y+2xy=6.求4x+8xy+9y=?
已知x+y=4,xy=-2,求代数式3(xy+2y)-(xy-6x)的值
已知x+y=4,xy=-2,求代数式3(xy+2y)-(xy-6x)
已知xy^2=-2,求-xy(x^2y^5-xy^3-y)的值.
已知xy^2=-2 求-xy(x^2y^5-xy^3-y)